2009
DOI: 10.1111/j.1439-0531.2009.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study in Immature Canine Oocytes Stained with Brilliant Cresyl Blue and Obtained From Bitches with Low and High Progesterone Serum Profiles

Abstract: This study was conducted: (i) to observe the features and levels of blue colour impregnation in morphologically selected immature canine cumulus oocyte complexes (COCs) stained with the brilliant cresyl blue (BCB) dye, as indicators of quality, and integrity of nuclear oocyte chromatin configuration before in vitro maturation (IVM); (ii) to observe the relationship between the influence of serum progesterone (SP) concentrations from ovary donors and BCB staining of immature dog oocytes. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…One association, evidenced in a variety of species, is the inverse relationship between G6PDH-activity and oocyte diameter [13,21,23,28,30] as observed in our study. Moreover, either oocyte volume [7], or size of originating follicle [31], associated with G6PDH-activity.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…One association, evidenced in a variety of species, is the inverse relationship between G6PDH-activity and oocyte diameter [13,21,23,28,30] as observed in our study. Moreover, either oocyte volume [7], or size of originating follicle [31], associated with G6PDH-activity.…”
Section: Discussionsupporting
confidence: 59%
“…Improvements in oocyte screening have been achieved in several species by application of BCB test [13,14,20,[27][28][29], a concept that we have successfully incorporated into the design of our study. To determine the validity of BCB test for in vitro ovine oocyte selection, G6PDH-activity was associated with oocyte diameter, meiotic competence and subsequent pre-implantation development.…”
Section: Discussionmentioning
confidence: 97%
“…BCB staining has been used for the selection of oocytes from several mammalian species. It was reported that BCB+ oocytes yielded a significantly higher blastocyst developmental rate than the BCB− and control oocytes in pig [2], goat [3], [4], sheep [5], mouse [6], dog [7], and bovine [1], [8][10]. However, whether BCB+ oocytes enhance the in vivo and full-term development of SCNT embryos and why BCB+ oocytes (with finished growth) are better than BCB- (growing oocytes) or non-treated oocytes (control oocytes) is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, BCB stains the cytoplasm blue or colorless depending on G6PDH activity [6, 7]. Research in pigs [79], goats [1012], cows [1316], mice [17], and dogs [18] indicate that the percentage of BCB+ oocytes reaching the blastocyst stage is significantly higher than BCB− oocytes. To our knowledge, there are no reports regarding the in vitro developmental competence of sheep oocytes selected using BCB staining.…”
Section: Introductionmentioning
confidence: 99%